2011
DOI: 10.1111/j.1365-3156.2010.02715.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of an algorithm based on WHO recommendations for the diagnosis of smear‐negative pulmonary tuberculosis in patients without HIV infection

Abstract: Summaryobjective To evaluate the performance of an algorithm based on WHO recommendations for diagnosis of smear-negative pulmonary tuberculosis in HIV-negative patients.methods We recruited HIV-negative patients with clinical suspicion of tuberculosis who had had three negative sputum smears in Lima, Peru. All included subjects underwent a complete anamnesis, physical examination and chest X-ray, and had a sputum specimen cultured in Ogawa, Middlebrook 7H9 media and MGITÒ. We applied an algorithm based on WHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…In Homa Bay, the clinical-radiological algorithm led to a high proportion of TB cases missed and a high proportion of patients overtreated. Our study is in line with most of the studies carried out in similar settings [6], [22], [25], [30] which have shown low algorithm sensitivity ranging from 23% to 59%. However, sensitivities of 80–95% have also been reported [23], [24].…”
Section: Discussionsupporting
confidence: 91%
“…In Homa Bay, the clinical-radiological algorithm led to a high proportion of TB cases missed and a high proportion of patients overtreated. Our study is in line with most of the studies carried out in similar settings [6], [22], [25], [30] which have shown low algorithm sensitivity ranging from 23% to 59%. However, sensitivities of 80–95% have also been reported [23], [24].…”
Section: Discussionsupporting
confidence: 91%
“…Two studies compared predefined rule-in algorithms against standard practice, both in a before–after design: one compared the proportions of smear-positive diagnoses before and after introducing a locally developed clinical algorithm in Ethiopia using routine notification data [21], and the other study compared hospitalization and mortality among severely ill HIV-infected individuals suspected to have TB, before and after introducing the WHO algorithm for diagnosis of smear-negative TB [22] in routine practice in South Africa [23]. Four other recent studies evaluated the 2007 WHO algorithm for ruling in smear-negative TB; one compared it to the 2003 WHO algorithm in Uganda [24], and the remaining three (from Brazil, Cambodia, and South Africa) used a non-comparative cross-sectional or retrospective design [25][27]. One study evaluated the most recent WHO-recommended algorithm for ruling out TB in HIV-infected individuals in Vietnam using a non-comparative design [28].…”
Section: Resultsmentioning
confidence: 99%
“…The clinical prediction rule, based on symptoms and chest X-ray findings, which we use in the algorithm has been evaluated previously as stand-alone tool (Soto et al 2011a). It identified well patients with high and low probabilities of SNPT and should permit to rationalise the use of liquid culture by reserving it for suspects with intermediate probability.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, over 10% had a final diagnosis of SNPT. Improvement must be viewed with caution and does not permit to exclude the disease, as also demonstrated in an evaluation of the current WHO algorithm for HIV-negative smear-negative SNPT suspects (Soto et al 2011b). In the present study, all SNPT patients could eventually be put on antituberculous treatment, but if culture is not performed in suspects who improve under broad-spectrum antibiotics, they are lost or their diagnosis will be seriously delayed.…”
Section: Discussionmentioning
confidence: 99%